Diklat Penguatan Kepemimpinan Aswaja, Membangun Kader NU yang Visioner, Moderat, dan Berdaya Guna di SMK Maarif Karangkobar, Banjarnegara - Suwarni, Titi (Abdibaraya, 2025)
This article discusses the importance of strengthening the leadership of Ahlussunnah wal Jama'ah (Aswaja) in the context of Nahdlatul Ulama (NU) cadre formation that is responsive to the challenges of the times. Aswaja's moderate and inclusive leadership is the main foundation in producing NU cadres who not only understand Islamic values in depth, but are also able to play an active role in various fields of social, political, and cultural life. With an approach based on the values of tawassuth (moderate), tasamuh (tolerant), tawazun (balanced), and i'tidal (fair), this article analyzes the strategy of strengthening leadership character and transforming cadre education that is visionary, adaptive, and effective. This study uses a qualitative-descriptive approach with a literature review and analysis of the thoughts of NU figures as a basis. The results of the study indicate that strengthening the identity of Aswaja and reformulating contextual cadre formation strategies are key steps in preparing the NU generation who are able to become future leaders who ground Islam rahmatan lil 'alamin